Anti-Judaism in Marcion and his Opponents - Tyson, Joseph B. (Studies in Christian-Jewish Relations, 2011)
Although Marcion is usually thought of as the arch-antisemite of the early church, this paper argues that his opponents were no less anti-Jewish than he. The proto-orthodox victory over Marcionite Christianity meant that the Hebrew Scriptures would continue to be a major part of the Christian canon and that Christians and might be encouraged to view the story of Jesus and their own faith as part of the history of ancient Israel. Marcion, by contrast, did not regard the Hebrew Scriptures as part of the Christian canon but nevertheless judged them to be accurate historical records that should be interpreted literally. In their rejection of Marcion, the proto-orthodox leaders also rejected a literal interpretation of the Hebrew Scriptures and sought to find an underlying unity between them and the Christian story. Despite the high status attributed to these Scriptures, Marcion’s opponents employed a variety of non-literal methods of interpretation, which generally carried with them a high degree of anti-Judaism. These tendencies may be observed both in the Acts of the Apostles, which is to be dated about 120 C.E., and Justin’s Dialogue with Trypho (c. 160 C.E.).